Serum AMH levels and insulin resistance in women with PCOS. (May 2018) - Sahmay, Sezai; Aydogan Mathyk, Begum; Sofiyeva, Nigar; Atakul, Nil; Azemi, Aslı; Erel, Tamer
Abstract: Objective: To compare the serum AMH levels between women with and without insulin resistance (IR) in polycystic ovary syndrome (PCOS). Study design: 293 women with PCOS according to the Rotterdam criteria were enrolled into our study. Insulin resistance was diagnosed according to the Homeostatic model assessment insulin resistant (HOMA-IR) formula and the cut-off point was set to more than 2.5. Women were grouped according to the presence of insulin resistance (IR) (HOMA-IR ≥ 2.5). Serum AMH and other hormones were compared between the IR (+) and IR (−) groups. Additionally, AMH percentiles were (<25, 25–75, >75) constructed; HOMA-IR and BMI values in women with/without IR were compared in different percentiles. Further, HOMA-IR, BMI and AMH values were measured across different PCOS phenotypes. Results: The prevalence of IR was 45%. The prevalence of IR was 57% in women with BMI ≥ 25. Serum AMH levels were not significantly different among women with and without IR. Also, HOMA-IR values were not significant among different AMH percentiles. However, in each AMH percentile BMI were found to be higher in women with IR than in women without IR. The median HOMA-IR values were the highest in women with BMI ≥ 25 in both IR (+) and IR (−) groups. No significant difference was found among PCOS phenotypes in terms of HOMA-IR and BMI. Positive correlations were found between BMI, free testosterone and HOMA-IR. However, no correlation was found between AMH and HOMA-IR. Conclusion: The serum AMH levels between women with IR and without IR in PCOS were not significantly different. Also, we did not reveal a correlation between serum AMH levels and IR in women with PCOS. IR was not correlated with different PCOS phenotypes either. We found a positive correlation between BMI and IR. IR should be investigated in women with PCOS having a BMI ≥ 25, independent of their phenotype or AMH levels.